Multisite Analysis of Lesions in the Respiratory Tract of the Rat and Nonhuman Primate (Cynomolgus Monkey) Exposed to Air, Vehicle, and Inhaled Small Molecule Compounds. (February 2021) - Gregori, Michela; Naylor, Stuart W.; Freke, Mark C.; Chamanza, Ronnie; Piaia, Alessandro; Hall, A. Peter
This paper presents a review of the nature, range, and incidences of background pathology findings in the respiratory tract of cynomolgus monkeys and rats. Data were collected from 81 inhalation studies and 133 non-inhalation studies evaluated at 3 geographically distinct contract research organization facilities. The inhalation studies were comprised of 44 different small molecule pharmaceuticals or chemicals which were also analyzed in order to understand the patterns of induced changes within the respiratory tract. The lung was the most frequently affected organ in both species, with increased alveolar macrophages being the most common background and test article–related finding. In the upper respiratory tract (URT), inflammatory cell infiltrates were the most common background findings in the nasal cavity in monkeys. Induced URT findings were more frequent in rats than monkeys, with squamous metaplasia in the larynx, and goblet cell hyperplasia in the nasal cavity being the most common. Overall, the data revealed a limited pattern of response to inhaled molecules in the respiratory tract, with background and test article–related findings often occurring in the same regions. It is hoped that these data will assist in the interpretation of findings in the respiratory tract induced by novel inhaled small molecule entities.